“Too little, too late”: youth retrospectives on school attendance problems and professional support received - Hamadi, Selina Eckhoff; Havik, Trude; Holen, Solveig (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionSchool attendance problems (SAPs) are a vexing issue that pose significant challenges for youth, families, and professional stakeholders. Despite growing research efforts, studies that explore the perspectives of youth on SAPs remain limited, particularly in Nordic countries. This qualitative study investigated Norwegian youths' retrospectives on the development and persistence of SAPs and the support they received from professionals in addressing their challenges.MethodsSemi-structured interviews were conducted with 10 youth (aged 12–22) with a history of SAPs in compulsory education. Participants were recruited by professionals from the educational-psychological service and alternative provisions in three Norwegian municipalities. Data were analyzed using reflexive thematic analysis.ResultsThe results indicate that lacking positive relationships with peers and teachers along with falling behind academically lead to school alienation and contributes to the onset or maintenance of SAPs. Similar experiences of gradual onset of SAPs, anxiety and depression, emotional and somatic distress, and conflicting feelings around avoidance were outlined. The youths’ initial experiences of support within the school setting were described as inappropriate, insufficient, or initiated too late, while attending alternative provisions appeared as a primary intervention that had enduring positive effects on attendance and engagement in academic and social activities.ConclusionThe findings highlight the need for early intervention, coherence between initiatives across support services and effective collaboration between youth, families, schools, and external services.